The Role of Individual Moral Cognition in Accounting Integrity: A Study on Ethical Decision-Making in China’s Evolving Economy - Yiyu, Liao; Yuheng, Huang; Qin, Zhong; Can, Huang (Siddhajyoti Interdisciplinary Journal, 2025)
Against the backdrop of China's economy transitioning towards stable and high-quality development, the importance of accounting integrity as a cornerstone trait has become increasingly prominent. This study delves into the complex dynamics of accounting and individual moral cognition, aiming to uncover the deeper societal, economic, and cultural roots behind decision-making in accounting practices and maintaining ethical standards. In this mixed methods approach, the data were gathered through quantitative survey and interviews and the data were analyzed using ANOVA and thematic analysis. The study findings reveal that the lack of accounting integrity is a multifaceted issue deeply rooted in the intricate interplay of societal norms, economic pressures, and individual ethics. Moreover, the results show that the level of individual moral cognitive development has an impact on accounting ethical decision-making. In conclusion, the findings of the study advocate for establishing a comprehensive governance system that addresses the underlying reasons for accounting integrity lapses, reshaping the accounting landscape by fostering a national climate of integrity and emphasizing ethical behavior in accounting practices to rebuild trust within the financial ecosystem.